Negotiating the greedy institution: a typology of the lived experiences of young, precarious academic workers. (2nd October 2018) - Bone, Kate; Jack, Gavin; Mayson, Susan
ABSTRACT: Coser's 'greedy institution' (GI) theory provides a conceptual lens to examine how institutional structures are negotiated and maintained by precarious workers in the contemporary university. Giddens' theory of structuration assists the analysis of empirical multi-case data generated from the Australian context where young academic workers were interviewed multiple times. This sociological analysis uniquely highlights the reciprocal and recursive processes that contribute to an agentic view of precarious employees who strategically navigate their careers and positions within prescriptive institutional structures. Findings supported the construction of a typology, comprising three agentic 'types'. The 'giving' and 'resisting' types presented depict how structures of greed encourage over-committed enactments from the participants. The 'insulated' type shows an antithetical portrayal of employment at the university, challenging often legitimated greedy norms in a way that highlights the role of supervisors in constructing workplace practices for precarious workers. The three 'types' reflect how participants complied with the demands of their work contexts in order to align their identities with institutional values. This article draws Coser into the precarious work literature and offers a socialised view of how the GI can be reproduced in differentiated ways through the agentic work of employees at the university.